2018
DOI: 10.1016/j.atmosenv.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative potential of ambient particulate matter in Beirut during Saharan and Arabian dust events

Abstract: In this study, we examine the oxidative potential of airborne particulate matter (PM) in Beirut, Lebanon, as influenced by dust events originating in the Sahara and Arabian deserts. Segregated fine (< 2.5 μm) and coarse (2.5-10 μm) PM samples collected during dust events, as well as during non-dust periods, were analyzed for chemical composition, and the alveolar macrophage (AM) assay was utilized to determine the oxidative potential of both types of samples. We performed Spearman rank-order correlation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 68 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…After they compared DTT activity of water‐soluble PM during Saharan dust events and nondust events, they inferred that Saharan dust has a lower DTT activity than the other sources on the site. Lovett et al () also examined the effects of Saharan and Arabian dust on the oxidative potential of PM in Beirut, Lebanon, although they used an assay that differs from DTT assay (alveolar macrophage assay) to measure the oxidative potential. They concluded that Saharan and Arabian dust events contribute minimally to the oxidative potential of PM in Beirut.…”
Section: Resultsmentioning
confidence: 99%
“…After they compared DTT activity of water‐soluble PM during Saharan dust events and nondust events, they inferred that Saharan dust has a lower DTT activity than the other sources on the site. Lovett et al () also examined the effects of Saharan and Arabian dust on the oxidative potential of PM in Beirut, Lebanon, although they used an assay that differs from DTT assay (alveolar macrophage assay) to measure the oxidative potential. They concluded that Saharan and Arabian dust events contribute minimally to the oxidative potential of PM in Beirut.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies showed that both POA and SOA have a substantial impact on OP v (refs. 7,62,[69][70][71][72][73][74][75][76][77] ). We find that aSOA has a higher OP m than bioSOA.…”
Section: Sources Of Opmentioning
confidence: 99%
“…Particulate matter (PM), especially PM 2.5 (aerodynamic equivalent diameter ≤2.5 μm), which is one of the main sources of air pollution, has raised serious concerns in the past years [1] , [2] , [3] . PM 2.5 has a great impact on human health, because toxic substances such as viruses, metals, and particles with various chemicals adsorbed onto PM surfaces tend to inhaled into the lungs [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%